2018
DOI: 10.1051/e3sconf/20184005019
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations on mixing of passive scalars in river confluences

Abstract: The study deals with the mixing of passive scalars (such as pollutants) in open-channel confluences when the two inflows exhibit different concentrations. The dispersion of such passive scalars is investigated through the analysis of the processes enhancing the mixing in the confluence in order to estimate the length for complete mixing Lm in the downstream branch. The aim of this study is then to establish a correlation between this length for complete mixing Lm and characteristics of the confluence, namely i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…As the helical cell from the CS becomes dominant, mixing occurs as flow from the KR is advected near the bed into flow from the lateral tributary ( Figure 3). The importance of curvature-induced helical motion for mixing at asymmetrical confluences has been noted in other field and numerical modeling studies (Chen et al, 2017;Jung et al, 2019), and modeling work has suggested that the strength of helical flow can directly control mixing length for both slow-and fast-mixing cases (Pouchoulin et al, 2018).…”
Section: Water Resources Researchmentioning
confidence: 83%
“…As the helical cell from the CS becomes dominant, mixing occurs as flow from the KR is advected near the bed into flow from the lateral tributary ( Figure 3). The importance of curvature-induced helical motion for mixing at asymmetrical confluences has been noted in other field and numerical modeling studies (Chen et al, 2017;Jung et al, 2019), and modeling work has suggested that the strength of helical flow can directly control mixing length for both slow-and fast-mixing cases (Pouchoulin et al, 2018).…”
Section: Water Resources Researchmentioning
confidence: 83%
“…In order to evaluate the mixing efficiency of pollutant, two indices were imposed for the assessment of mixing rate along the channel. The normalized root mean square of concentration Cm within the profile is an effective parameter to quantify the uniformity of the pollutant's spatial distribution, which have been widely used in similar studies [33,34]. The definition of Cm can be expressed by: ( )…”
Section: Mixing Efficiencymentioning
confidence: 99%
“…To quantify the non-uniformity of mixing downstream of the confluence, the dimensionless parameter E, used e.g. by Dalmon et al (2015) and Pouchoulin et al (2018), is adopted in the present work:…”
Section: Mixing Of the Passive Scalarmentioning
confidence: 99%
“…Both the flow and the mixing of a passive scalar will be investigated by means of Large Eddy Simulation (LES). Moreover, the spatial focus of this paper will not be mainly devoted to the CHZ, as in Tang et al (2018), but will also extend somewhat further downstream, though not as far as needed for studying the length for complete mixing, as in Pouchoulin et al (2018). (= 0.4m) is larger than the width W (= 0.3m) of the main upstream channel and the tributary channel, as shown schematically in Figure 1.…”
Section: Introductionmentioning
confidence: 99%